Titanium carbide nanofilm and its preparation method and application

By using electrospinning technology on the carbon felt of vanadium battery electrodes, the problem of insufficient performance of vanadium battery electrodes is solved, and higher conductivity, mechanical properties and corrosion resistance are achieved, and the service life of the battery electrodes is extended.

CN116377604BActive Publication Date: 2025-03-14CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211671815.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-03-14
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

The performance of existing vanadium battery electrodes is insufficient, which affects the charging and discharging efficiency and life of vanadium battery.

Method used

Electrospinning technology is used to prepare titanium carbide nanofilms on carbon felt to form three-dimensional nanofilms to improve the conductivity, mechanical properties and corrosion resistance of the electrodes.

Benefits of technology

It effectively improves the conductivity, mechanical properties and corrosion resistance of vanadium battery electrodes, extends the service life and efficiency of the battery electrodes, and maintains the porosity of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377604B_ABST
    Figure CN116377604B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials for vanadium flow batteries, and in particular to a titanium carbide nanofilm and a preparation method and application thereof. The present invention uniformly mixes titanium carbide nanopowder into a relevant liquid matrix to form a uniform and stable nanofluid, and then prepares the solution on the surface of carbon felt, a substrate material for vanadium battery electrodes, through an electrostatic spinning technique with specific parameters to form a layer of uniform and thin three-dimensional nanofilm, and applies the prepared new electrode to a vanadium battery system. The present invention prepares a titanium carbide three-dimensional nanofilm on carbon felt and applies it to vanadium battery electrode materials, which can effectively improve the electrical conductivity, mechanical properties, corrosion resistance, etc. of vanadium battery electrodes, and extend the service life and efficiency of battery electrodes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new materials technology for vanadium redox flow batteries, and in particular to a titanium carbide nanofilm, its preparation method, and its application. Background Technology

[0002] Titanium carbide (TiC) is an iron-gray crystal with a metallic luster. It has several metal-like properties, such as high melting point, boiling point and hardness, and its hardness is second only to diamond. It also has good thermal and electrical conductivity and exhibits superconductivity at extremely low temperatures. It also has high strength, high hardness, wear resistance, high temperature resistance, oxidation resistance and chemical stability, as well as the toughness of metal. Therefore, it is widely used in many fields such as high-temperature structural ceramic materials, alloy composite materials, functional materials, refractory materials and nuclear control materials. The application range of titanium carbide is as follows: (1) Cutting metal tools: The new titanium carbide-based cermet is a tool material that has developed rapidly in recent years. It has high comprehensive performance and its wear resistance is much higher than that of ordinary cemented carbide under the same cutting conditions. It is also 5 to 8 times more wear-resistant than YT14 and YT15 cemented carbide when cutting at high speed. At present, titanium carbide-based cermet has been made into various inserts for precision boring of holes and precision machining fields such as "turning instead of grinding". (2) Aerospace industry: TiC / Cu cermets prepared by high-temperature sintering skeleton melting process have good ablation resistance and have the potential to be used as rocket throat liners and protective plates. (3) Others: Metal matrix lining ceramics synthesized by SHS centrifugal casting can be used as anti-corrosion pipes for the transportation of petroleum or chemical products and semi-finished products. They can also be used as wear-resistant pipes in mines and mineral processing plants for slurry transportation. They can also be used for water pipelines with a lot of mud and sand. Johnson et al. found that the room temperature yield strength of Ti-37 vol.% TiC composite material was 11% higher than that of the matrix, the tensile strength was 573 MPa, the elongation was 1.9%, and they believed that the fracture of the composite material at any temperature was due to the fracture of the reinforcing phase. Castro et al. prepared TiC-reinforced titanium matrix composites with different volume fractions using a melting and casting method. They found that when the volume fraction of the reinforcing phase was 2.1%, the presence of fine TiC particles eliminated dendrite formation, refined the matrix structure, and thus improved the room temperature plasticity of the material. The elongation of the composites with other reinforcing phase contents was lower than that of the titanium matrix, and the high-temperature mechanical properties of the materials at 450℃ were superior to those of pure titanium.

[0003] my country's vanadium battery technology is generally in a leading position internationally, and it has basically formed a vanadium battery energy storage industry chain and corresponding technical support system. Currently, it is in a critical development stage of leaping towards industrialization. To meet the needs of energy development strategy and industrialization, it is necessary to reduce preparation and transportation costs based on existing research, develop key materials for vanadium battery energy storage, and develop integrated application technologies for vanadium battery energy storage, connecting with the industrial application and demonstration verification of vanadium battery energy storage.

[0004] Electrode development is one of the most critical technologies for the large-scale application of vanadium batteries. Among the patented technologies for vanadium batteries, the area of ​​continuous upgrading and optimization of electrodes is also the fastest-evolving. The electrolyte in a vanadium battery is both the energy carrier and the reactive material, determining the battery's capacity and directly affecting its charge-discharge efficiency and lifespan. Therefore, the performance of the electrodes, which are in direct contact with the electrolyte, is particularly important.

[0005] In conclusion, there is an urgent need for a material to improve the performance of vanadium battery electrodes. Summary of the Invention

[0006] To address the above problems, this invention provides a titanium carbide nanofilm, its preparation method, and its applications.

[0007] A method for preparing titanium carbide nanofilms, the method comprising:

[0008] A certain amount of titanium carbide nanoparticles with a uniform particle size range were dispersed in a base liquid to prepare a titanium carbide nanoparticle solution with a concentration of 0.05-0.35 mol / L.

[0009] The titanium carbide nanoparticle solution was prepared into a uniform and stable titanium carbide nanofluid by magnetic stirring and ultrasonic vibration using an ultrasonic crusher.

[0010] Titanium carbide nanofluid is added to a plastic syringe equipped with a plastic capillary needle. The carbon felt is fixed on an electrospinning table with the needle at a certain distance from the spinning table. After spinning, the spun sample is placed in an oven to dry, thus producing a three-dimensional titanium carbide nanofilm on the carbon felt.

[0011] Furthermore, the base solution is configured as a mixture of DMF, polyvinylpyrrolidone (PVP), and ethanol solution, with a molar ratio of 1:1:(5-10).

[0012] Furthermore, the preparation of the base solution specifically includes: slowly adding PVP dried at 30-50℃ for 1-2 hours to anhydrous ethanol solution, adding a certain amount of DMF solution, and magnetically stirring until the PVP is completely dissolved to form a transparent, homogeneous, colorless solution.

[0013] Furthermore, the titanium carbide nanoparticles within a certain uniform particle size range are either less than or equal to 30 nm or less than or equal to 50 nm.

[0014] Furthermore, the titanium carbide nanoparticles include spherical or fibrous titanium carbide nanoparticles.

[0015] Furthermore, the step of preparing a uniform and stable titanium carbide nanofluid by magnetic stirring and ultrasonic vibration using an ultrasonic crusher specifically includes:

[0016] The titanium carbide nanoparticle solution was magnetically stirred for 15-30 minutes and then ultrasonically vibrated for 30-120 minutes using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid.

[0017] Furthermore, the process of adding titanium carbide nanofluid into a plastic syringe equipped with a plastic capillary needle, fixing the carbon felt on an electrospinning table with the needle at a certain distance from the spinning table, and drying the spun sample in an oven after spinning is completed includes:

[0018] Add 2-8 ml of titanium carbide nanofluid to a plastic syringe. The syringe is equipped with a plastic capillary needle with an orifice diameter of 0.4-1 mm. Fix the carbon felt on an electrospinning table with the needle 10-15 cm away from the table. The electrostatic voltage is controlled at 10-15 kV. After spinning, place the spun sample in an oven and dry it at 50-80°C for 2-5 hours to obtain a three-dimensional titanium carbide nanofilm on the carbon felt.

[0019] A titanium carbide nanofilm, wherein the three-dimensional titanium carbide nanofilm is prepared by the above-described method for preparing a titanium carbide nanofilm.

[0020] An application of titanium carbide nanofilms,

[0021] The three-dimensional titanium carbide nanofilm on the carbon felt is cut according to the size of the vanadium battery flow frame and assembled to obtain the vanadium battery;

[0022] The titanium carbide three-dimensional nanofilm was prepared using one of the above-described methods for preparing titanium carbide nanofilms.

[0023] The present invention has at least the following beneficial effects:

[0024] The three-dimensional titanium carbide nanofilm prepared by this invention possesses characteristics such as uniform structure, stable physicochemical properties, and superior mechanical properties. It is mainly used as a self-supporting surface layer for the positive and negative electrode materials of vanadium redox batteries. A nanoscale titanium carbide film is deposited on ordinary carbon felt using electrospinning technology, effectively improving the conductivity, mechanical properties, and corrosion resistance of the carbon felt, without affecting the porosity of the electrode itself or the cycle efficiency and energy density of the vanadium redox flow battery. Furthermore, this technology can be extended to other battery electrode fields. Vanadium redox flow battery energy storage is a necessary trend for the future development of large-scale energy storage, with a huge market both domestically and internationally. It offers safe and environmentally friendly operating temperatures, long service life, and recyclability; therefore, superior battery electrodes are extremely important, and this technology has broad application prospects.

[0025] The three-dimensional titanium carbide nanofilm prepared by this invention can effectively improve the conductivity, mechanical properties, and corrosion resistance of vanadium battery electrodes, extending their lifespan and efficiency. Electrode development is one of the most critical technologies for the large-scale application of vanadium batteries, and the area with the fastest pace of technological updates in vanadium battery patents is the continuous upgrading and optimization of electrodes. The vanadium battery electrolyte is both the energy carrier and the reactive material, determining the battery's capacity and directly affecting its charge-discharge efficiency and lifespan. Therefore, the performance of the electrodes, which are in direct contact with the electrolyte, is particularly important. This technology can be successfully applied to the field of vanadium battery energy storage and can also be applied to the field of traditional batteries. The application of this research will greatly contribute to economic development and significantly improve people's quality of life.

[0026] This invention prepares a three-dimensional titanium carbide nanofilm on a carbon felt, which can be applied to vanadium battery electrode materials to effectively improve the conductivity, mechanical properties, corrosion resistance, etc. of vanadium battery electrodes, and extend the service life and efficiency of the battery electrodes.

[0027] This method involves uniformly mixing titanium carbide nanoparticles into a relevant liquid matrix to form a uniform and stable nanofluid. Then, the solution is prepared on the surface of the carbon felt substrate material of the vanadium battery electrode using electrospinning technology with specific parameters, forming a uniform and thin three-dimensional nanofilm. The prepared novel electrode is then applied to the vanadium battery system.

[0028] Compared with traditional vanadium battery electrodes, the titanium carbide thin film electrode prepared by this invention has better conductivity. Titanium carbide itself also has good thermal conductivity, which is beneficial for the multiple cycles of vanadium batteries and extends their service life.

[0029] The titanium carbide thin-film electrode prepared by this invention exhibits superior corrosion resistance. Vanadium battery electrolytes are primarily composed of concentrated sulfuric acid or concentrated hydrochloric acid, which are highly corrosive. Preparing a three-dimensional titanium carbide nanofilm on a carbon felt significantly improves the electrode's corrosion resistance.

[0030] The titanium carbide thin film electrode prepared by this invention does not affect the porosity of the vanadium battery system after use, and can still maintain a porosity of more than 95%, ensuring the normal circulation of the electrolyte.

[0031] The present invention prepares a three-dimensional network structure of titanium carbide nanofilm based on carbon felt, which has the advantages of high mechanical strength and long-term cycle stability.

[0032] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures pointed out in the description and the drawings. Attached Figure Description

[0033] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0034] Figure 1 This is a flowchart illustrating the preparation method of three-dimensional titanium carbide nanofilms according to an embodiment of the present invention. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Electrode development is one of the most critical technologies for the large-scale application of vanadium batteries. Among the patented technologies for vanadium batteries, the area of ​​continuous upgrading and optimization of electrodes is also the fastest-evolving. The electrolyte in a vanadium battery is both the energy carrier and the reactive material, determining the battery's capacity and directly affecting its charge-discharge efficiency and lifespan. Therefore, the performance of the electrodes, which are in direct contact with the electrolyte, is particularly important.

[0037] Therefore, this invention proposes a titanium carbide nanofilm, its preparation method, and its application, including a titanium carbide nanofilm, a method for preparing a titanium carbide nanofilm, and an application of a titanium carbide nanofilm.

[0038] This invention prepares a three-dimensional titanium carbide nanofilm on a carbon felt for use as an electrode material in vanadium battery. This effectively improves the conductivity, mechanical properties, and corrosion resistance of the vanadium battery electrode, extending its lifespan and efficiency. The method involves uniformly mixing titanium carbide nanoparticles into a relevant liquid matrix to form a homogeneous and stable nanofluid. Then, using electrospinning technology with specific parameters, the solution is applied to the surface of the carbon felt substrate material for the vanadium battery electrode, forming a uniform and thin three-dimensional nanofilm. The prepared novel electrode is then applied to a vanadium battery system.

[0039] To enable those skilled in the art to better understand the present invention, the principles of the present invention are explained below in conjunction with specific embodiments:

[0040] In a first aspect, the present invention provides a method for preparing titanium carbide nanofilms.

[0041] like Figure 1 As shown, a certain amount of titanium carbide nanoparticles with a uniform particle size range are dispersed in a base liquid to prepare a titanium carbide nanoparticle solution with a concentration of 0.05-0.35 mol / L.

[0042] The titanium carbide nanoparticle solution was prepared into a uniform and stable titanium carbide nanofluid by magnetic stirring and ultrasonic vibration using an ultrasonic crusher.

[0043] Titanium carbide nanofluid is added to a plastic syringe equipped with a plastic capillary needle. The carbon felt is fixed on an electrospinning table with the needle at a certain distance from the spinning table. After spinning, the spun sample is placed in an oven to dry, thus producing a three-dimensional titanium carbide nanofilm on the carbon felt.

[0044] In specific implementation, the titanium carbide nanoparticles mentioned in this invention are of a size of 30 nm or less or 50 nm, and can be obtained by screening using equipment such as molecular sieves.

[0045] Specific implementation examples are as follows:

[0046] Implementation Plan 1:

[0047] Step 1: Slowly add PVP dried at 40℃ for 1 hour to anhydrous ethanol solution, and add a certain amount of DMF solution. Stir magnetically until PVP is completely dissolved to form a transparent, homogeneous, colorless solution A, in which the molar ratio of DMF:PVP:anhydrous ethanol = 1:1:5.

[0048] Step 2: Disperse titanium carbide nanoparticles (particle size less than or equal to 50 nm, spherical) in the above colorless solution A at a concentration of 0.1 mol / L, stir magnetically for 25 min, and then ultrasonically vibrate for 30 min using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid B.

[0049] Step 3: Add 6 ml of the previously prepared titanium carbide nanofluid B to a plastic syringe. The syringe is fitted with a plastic capillary tube at the tip, and the needle can be 0.8 mm. Fix the carbon felt on an electrospinning table, with the needle 15 cm away from the spinning table. The voltage between them is controlled at 15 kV. After spinning, place the spun sample in an oven and dry it at 80°C for 2 hours. This will produce a three-dimensional titanium carbide nanofilm on the carbon felt, forming substance C.

[0050] Step 4: Cut the pre-made carbon felt (C) to the size of the vanadium battery flow frame, assemble the vanadium battery, and test it after assembly. Test its capacity by cycling it 200 times at a current density of 0.2 A / g; the capacity remained unchanged. Simultaneously, test the porosity of the newly made electrode before and after use: 95%; corrosion protection efficiency: 98.2%; conductivity improvement: 76%.

[0051] Implementation Plan Two:

[0052] Step 1: Slowly add PVP dried at 50℃ for 1 hour to anhydrous ethanol solution, and add a certain amount of DMF solution. Stir magnetically until PVP is completely dissolved to form a transparent, homogeneous, colorless solution A, in which the molar ratio of DMF:PVP:anhydrous ethanol = 1:1:6.

[0053] Step 2: Disperse titanium carbide nanoparticles (particle size less than or equal to 30 nm, fibers) in the above colorless solution A at a concentration of 0.15 mol / L, stir magnetically for 30 min, and then ultrasonically vibrate for 60 min using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid B.

[0054] Step 3: Add 8 ml of the previously prepared titanium carbide nanofluid B to a plastic syringe. The syringe is fitted with a plastic capillary tube at the tip, and the needle can be 0.8 mm. Fix the carbon felt on an electrospinning table, with the needle 10 cm away from the table. The voltage between the needle and the table is controlled at 15 kV. After spinning, place the spun sample in an oven and dry it at 70°C for 2 hours. This will produce a three-dimensional titanium carbide nanofilm on the carbon felt, forming substance C.

[0055] Step 4: Cut the pre-made carbon felt (C) to the size of the vanadium battery flow frame, assemble the vanadium battery, and test it after assembly. Test its capacity by cycling it 300 times at a current density of 0.2 A / g; the capacity remained unchanged. Simultaneously, test the porosity of the newly made electrode before and after use: 96%; corrosion protection efficiency: 99.2%; conductivity increase: 73%.

[0056] Implementation Plan 3:

[0057] Step 1: Slowly add PVP dried at 40℃ for 1.5h to anhydrous ethanol solution, and add a certain amount of DMF solution. Stir magnetically until PVP is completely dissolved to form a transparent, homogeneous, colorless solution A, in which the molar ratio of DMF:PVP:anhydrous ethanol = 1:1:8.

[0058] Step 2: Disperse titanium carbide nanoparticles (particle size less than or equal to 50 nm, spherical) in the above colorless solution A at a concentration of 0.2 mol / L, stir magnetically for 15 min, and then ultrasonically vibrate for 90 min using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid B.

[0059] Step 3: Add 7 ml of the previously prepared titanium carbide nanofluid B to a plastic syringe. The syringe is fitted with a plastic capillary tube at the tip, and the needle can be 0.6 mm. Fix the carbon felt on an electrospinning table, with the needle 12 cm away from the table. The voltage between them is controlled at 10 kV. After spinning, place the spun sample in an oven and dry it at 80°C for 3 hours. This will produce a three-dimensional titanium carbide nanofilm on the carbon felt, forming substance C.

[0060] Step 4: Cut the pre-made carbon felt C according to the size of the vanadium battery flow frame, assemble the vanadium battery, and test it after assembly. Test its capacity by cycling it 400 times at a current density of 0.1 A / g; the capacity remains unchanged. Simultaneously, test the porosity of the newly made electrode before and after use: 96%; corrosion protection efficiency: 99.1%; conductivity increase: 77%.

[0061] Implementation Plan Four:

[0062] Step 1: Slowly add PVP dried at 50℃ for 1.5h to anhydrous ethanol solution, and add a certain amount of DMF solution. Stir magnetically until PVP is completely dissolved to form a transparent, homogeneous, colorless solution A, in which the molar ratio of DMF:PVP:anhydrous ethanol = 1:1:10.

[0063] Step 2: Disperse titanium carbide nanoparticles (particle size less than or equal to 50 nm, spherical) in the above colorless solution A at a concentration of 0.25 mol / L, stir magnetically for 20 min, and then ultrasonically vibrate for 100 min using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid B.

[0064] Step 3: Add 8 ml of the previously prepared titanium carbide nanofluid B to a plastic syringe. The syringe is fitted with a plastic capillary tube at the tip, and the needle can be 0.8 mm. Fix the carbon felt on an electrospinning table, with the needle 10 cm away from the table. The voltage between them is controlled at 10 kV. After spinning, place the spun sample in an oven and dry it at 80°C for 4 hours. This will produce a three-dimensional titanium carbide nanofilm on the carbon felt, forming substance C.

[0065] Step 4: Cut the pre-made carbon felt C according to the size of the vanadium battery flow frame, assemble the vanadium battery, and test it after assembly. Test its capacity by cycling it 400 times at a current density of 0.2 A / g; the capacity remains unchanged. Simultaneously, test the porosity of the newly made electrode before and after use: 95%; corrosion protection efficiency: 98.3%; conductivity increase: 80%.

[0066] Secondly, the present invention provides a titanium carbide nanofilm, wherein the three-dimensional titanium carbide nanofilm is prepared by the above method.

[0067] Thirdly, this invention provides an application of titanium carbide nanofilms. The three-dimensional titanium carbide nanofilms prepared on the carbon felt are cut to the size of the vanadium battery flow frame, and a vanadium battery is assembled. After assembly, testing is performed, testing its capacity by cycling 200-400 times at a current density of 0.1 A / g–0.2 A / g. Simultaneously, the porosity, corrosion resistance, conductivity, and other parameters of the newly fabricated electrode before and after use are tested.

[0068] The three-dimensionality mentioned in this invention refers to the fact that the formed thin film is a three-dimensional network material. The titanium carbide thin film provided by this invention uses carbon felt as a substrate and is specifically designed for vanadium redox flow battery electrodes.

[0069] The titanium carbide thin film electrode prepared by this invention has excellent electrical conductivity, and titanium carbide itself has good thermal conductivity, which is beneficial for the multiple cycles of vanadium batteries and extends their service life.

[0070] The titanium carbide thin-film electrode prepared by this invention exhibits superior corrosion resistance. Vanadium battery electrolytes are primarily composed of concentrated sulfuric acid or concentrated hydrochloric acid, which are highly corrosive. Preparing a three-dimensional titanium carbide nanofilm on a carbon felt significantly improves the electrode's corrosion resistance.

[0071] The titanium carbide thin film electrode prepared by this invention does not affect the porosity of the vanadium battery system after use, and can still maintain a porosity of more than 95%, ensuring the normal circulation of the electrolyte.

[0072] The present invention prepares a three-dimensional network structure of titanium carbide nanofilm based on carbon felt, which has the advantages of high mechanical strength and long-term cycle stability.

[0073] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a titanium carbide nanofilm, characterized in that: The method comprises: Dispersing a certain amount of titanium carbide nanoparticles with a uniform particle size range in a base liquid to prepare a titanium carbide nanoparticle solution with a concentration of 0.05-0.35 mol / L; The titanium carbide nanoparticle solution is subjected to magnetic stirring and ultrasonic oscillation by an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid; Add titanium carbide nanofluid into a plastic syringe equipped with a plastic capillary needle, fix the carbon felt on an electrospinning table, and keep the needle at a certain distance from the spinning table. After the spinning is completed, put the spun sample into an oven for drying, thus forming a titanium carbide three-dimensional nanofilm on the carbon felt. The base liquid is configured as a mixture of DMF, polyvinylpyrrolidone PVP and ethanol solution, with the molar ratio being 1:1:(5-10) respectively; The base liquid preparation specifically includes: slowly adding PVP dried at 30-50° C. for 1-2 hours into an anhydrous ethanol solution, adding a certain amount of DMF solution, and magnetically stirring until the PVP is completely dissolved to form a transparent and uniform colorless solution; The titanium carbide nanoparticles of a certain uniform particle size range are one of less than or equal to 30 nm or less than or equal to 50 nm.

2. The method for preparing a titanium carbide nanofilm according to claim 1, characterized in that: The titanium carbide nanoparticles include spherical or fibrous titanium carbide nanoparticles.

3. The method for preparing a titanium carbide nanofilm according to claim 1, characterized in that: The titanium carbide nanoparticle solution is subjected to magnetic stirring and ultrasonic oscillation by an ultrasonic crusher to prepare the titanium carbide nanoparticle solution into a uniform and stable titanium carbide nanofluid, specifically comprising: The titanium carbide nanoparticle solution is magnetically stirred for 15-30 minutes and ultrasonically oscillated for 30-120 minutes using an ultrasonic crusher to prepare a uniform and stable titanium carbide nanofluid.

4. The method for preparing a titanium carbide nanofilm according to claim 1, characterized in that: The titanium carbide nanofluid is added to a plastic syringe equipped with a plastic capillary needle, the carbon felt is fixed on an electrostatic spinning table, the needle is at a certain distance from the spinning table, and after the spinning is completed, the spun sample is placed in an oven for drying, specifically comprising: Take 2-8 ml of titanium carbide nanofluid and add it to a plastic syringe. The front end of the syringe is equipped with a plastic capillary needle with an aperture of 0.4-1 mm. Fix the carbon felt on the electrostatic spinning table with the needle 10-15 cm away from the spinning table. The electrostatic voltage is controlled at 10-15 kV. After the spinning is completed, put the spun sample into an oven and dry it at 50℃-80℃ for 2-5 hours to form a three-dimensional titanium carbide nanofilm on the carbon felt.

5. A titanium carbide nanofilm, characterized in that: The titanium carbide three-dimensional nanofilm is prepared by the method for preparing a titanium carbide nanofilm according to any one of claims 1 to 4.

6. An application of titanium carbide nanofilm, characterized in that: The titanium carbide three-dimensional nanofilm on the carbon felt is cut according to the size of the vanadium battery liquid flow frame, and assembled to obtain a vanadium battery; The titanium carbide three-dimensional nanofilm is prepared by the method for preparing a titanium carbide nanofilm according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparation method of multifunctional nanometer paper / static electric spinning fiber flexible composite film structure

    CN105908490A

  • Carbon nanotube self-assembly nanofiber felt and preparation and application thereof

    CN106876733A